2015
DOI: 10.3390/s151128842
|View full text |Cite
|
Sign up to set email alerts
|

A Room-Temperature Operation Formaldehyde Sensing Material Printed Using Blends of Reduced Graphene Oxide and Poly(methyl methacrylate)

Abstract: This work demonstrates a printable blending material, i.e., reduced graphene oxide (RGO) mixed with poly(methyl methacrylate) (PMMA), for formaldehyde sensing. Based on experimental results, 2% RGO/10% PMMA is an optimal ratio for formaldehyde detection, which produced a 30.5% resistance variation in response to 1000 ppm formaldehyde and high selectivity compared to different volatile organic compounds (VOCs), humidity, CO, and NO. The demonstrated detection limit is 100 ppm with 1.51% resistance variation. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…CMC with amino groups was introduced to reduce hydrophilic GO, and thus improve the conductivity of the hydrogels [ 25 ]. TEM images showed the presence of dark patches after the combination of GO with CMC ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
“…CMC with amino groups was introduced to reduce hydrophilic GO, and thus improve the conductivity of the hydrogels [ 25 ]. TEM images showed the presence of dark patches after the combination of GO with CMC ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
“…While few if any of these techniques were aimed specifically at applications in phones or wearables, some have potential for these uses, being small, sensitive and potentially low cost. For example, workers from the National Taiwan University showed that films of RGO mixed with poly(methyl methacrylate) (PMMA) in the ratio 2 per cent RGO:10 per cent PMMA exhibited a resistance change of 30.5 per cent when exposed to 1,000 ppm formaldehyde (Chuang et al, 2015). The sensor operated at room temperature, and the limit of detection was 100 ppm which led to a 1.51 per cent resistance variation.…”
Section: Innovations In Gas Sensingmentioning
confidence: 99%
“…Indeed, graphene/metal oxides based composites could improve the sensitivity of formaldehyde sensor because of the electron transfer channels provided by the metal oxide such as SnO [40], SnO 2 [39,41,42], TiO 2 [43][44][45], and ZnO [46][47][48] and ZnSnO 3 [49]. Besides, the graphene has formed composites with polymers [50][51][52], Si nanowires [53] and MoS 2 [54,55] to serve as formaldehydesensing materials. However, the oxygen plasma treated 3D graphene has yet applied in formaldehyde sensing.…”
Section: Introductionmentioning
confidence: 99%